2007
DOI: 10.1164/rccm.200702-334oc
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β1 Suppresses Airway Hyperresponsiveness in Allergic Airway Disease

Abstract: Rationale: Asthma is characterized by increases in airway resistance, pulmonary remodeling, and lung inflammation. The cytokine transforming growth factor (TGF)-b has been shown to have a central role in asthma pathogenesis and in mouse models of allergic airway disease. Objectives: To determine the contribution of TGF-b to airway hyperresponsiveness (AHR), we examined the time course, source, and isoform specificity of TGF-b production in an in vivo mouse asthma model. To then elucidate the function of TGF-b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
90
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 58 publications
14
90
1
Order By: Relevance
“…Consistent with our findings in children with asthma, Ogawa and colleagues reported that the CC genotype of SNP rs1800469 was associated with increased airway responsiveness in 590 adults with COPD (33). If allele C of SNP rs1800469 is in fact correlated with reduced levels of TGF-b1 (see below), our findings and those of Ogawa and colleagues are consistent with those of murine models of allergic airway inflammation that suggest that antagonism of TGF-b1 results in increased airway responsiveness (34), and that intratracheal administration of TGF-b1 inhibits antigeninduced airway responsiveness (35). * All analyses were conducted under the assumption of a dominant genetic model.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our findings in children with asthma, Ogawa and colleagues reported that the CC genotype of SNP rs1800469 was associated with increased airway responsiveness in 590 adults with COPD (33). If allele C of SNP rs1800469 is in fact correlated with reduced levels of TGF-b1 (see below), our findings and those of Ogawa and colleagues are consistent with those of murine models of allergic airway inflammation that suggest that antagonism of TGF-b1 results in increased airway responsiveness (34), and that intratracheal administration of TGF-b1 inhibits antigeninduced airway responsiveness (35). * All analyses were conducted under the assumption of a dominant genetic model.…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, airway reactivity was shown to correlate negatively with airway wall thickness in humans with asthma (155,175). Similar observations were made in a mouse model of asthma (2). Therefore, even if thickening due to fibrosis can theoretically increase airway narrowing in response to spasmogens because of geometrical effects, airway wall stiffening due to thicker or more fibrotic wall may well protect against AHR.…”
Section: Reduced Asm-load Due To Remodelingsupporting
confidence: 54%
“…In contrast, Alcorn and coworkers have indicated that attenuated airway remodeling does not impact airway inflammatory responses or AHR (27). In particular, these authors reported that neutralization of TGF-b1 responses in the lungs of OVA-treated mice suppressed airway fibrosis while increasing AHR; neutralization had no affect on airway inflammation (27). Collectively, these studies demonstrate that airway inflammation, remodeling, and hyperresponsiveness may not be directly interrelated.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, Leigh and coworkers have shown that mice that undergo chronic allergen exposure exhibit structural changes that are associated with AHR in the absence of cellular inflammation (26). In contrast, Alcorn and coworkers have indicated that attenuated airway remodeling does not impact airway inflammatory responses or AHR (27). In particular, these authors reported that neutralization of TGF-b1 responses in the lungs of OVA-treated mice suppressed airway fibrosis while increasing AHR; neutralization had no affect on airway inflammation (27).…”
Section: Discussionmentioning
confidence: 99%